PCR from fungal spores after microwave treatment - Adlane Ferreira; V. B. Glass; N. Louise (Fungal Genetics Reports, 1996)
We describe a fast template preparation method for PCR amplification from fungal spores using microwave irradiation. The method is useful when the availability of fungal material is restricted or the number of processed samples is large.